2011
DOI: 10.4111/kju.2011.52.7.457
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Can Be Detected Even in Patients with Decreased PSA Less than 2.5 ng/ml after Treatment of Chronic Prostatitis

Abstract: PurposeWe evaluated men with documented chronic prostatitis and elevated serum prostate-specific antigen (PSA) to determine whether treatment with antibiotics and anti-inflammatory drugs can lower serum PSA and the cancer detection rate in patients with post-treatment PSA <4 ng/ml.Materials and MethodsEighty-six men who presented with serum PSA greater than 4 ng/ml and who were subsequently diagnosed with chronic prostatitis with greater than 10 white blood cells per high power field in expressed prostatic exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 18 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…The majority of studies were retrospective and nine studies were randomised controlled trials (RCTs) [4][5][6][7][8][9][10][11][12]. Furthermore, there were seven prospective non-randomised trials [13][14][15][16][17][18][19]. All studies reported on the variables indicated in the data extraction section and are listed in Table 1 [4-32, 34, 35].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of studies were retrospective and nine studies were randomised controlled trials (RCTs) [4][5][6][7][8][9][10][11][12]. Furthermore, there were seven prospective non-randomised trials [13][14][15][16][17][18][19]. All studies reported on the variables indicated in the data extraction section and are listed in Table 1 [4-32, 34, 35].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies used ofloxacin [4,8,10,13,15,16], six studies used 500 mg ciprofloxacin [5,9,17,19,21,23], and five used levofloxacin [6,9,12,28]. Six studies combined the antibiotic therapy with NSAIDs [4,5,18,20,23,25]. Huang et al [21] added the plant extracts, Ningbitai and Yunnan Baiyao capsule, to the antibiotic therapy.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al [16] showed that the mean PSA concentration decreased significantly after 4 weeks of treatment with antibiotics and nonsteroidal anti-inflammatory agents. A relatively high rate of cancer (13.5%, 5/37) was detected in patients with a PSA value that decreased to a normal value (<4 ng/mL) after treatment.…”
Section: Discussionmentioning
confidence: 99%